Discontinuation of implants and associated factors among women in health facilities of Bahir Dar city, Northwest Ethiopia: A cross-sectional study - Yilkal Dagnaw Melesse; Melkamu Addis Adamu; Mastewal Yechale Mihret; Zelalem Feleke Wudu (Elsevier, 2024)
Introduction: Discontinuation of implants is the removal or switch to other methods before duration completion. Despite the improvement in the utilization of implants, discontinuation is high. There are limited studies conducted on implant discontinuation and factors in Bahir Dar City. This research aimed to evaluate the proportion and explanatory variables of discontinuation of implants among users in health facilities in Bahir Dar City, Ethiopia. Methods: A health facility-based cross-sectional design was conducted on 415 respondents from April 1 to May 30, 2021. Data were collected through face-to-face interview questionnaires using a systematic random sampling method. Epi Data version 3.1 and Statistical Package for Social Sciences were used for data entry and formal analysis, respectively. Logistic regression analyses were used, and a P value less than 0.05 was considered a statistically significant factor for discontinuation. Results: The overall proportion of discontinuation of implants was 55.3 % (95 % CI: 61.42-69.13). In bivariate logistic regression analysis, sociocultural factors like maternal religion and occupation, were factors for discontinuation of implants. After adjusting other variables in multivariate regression analysis, no formal education (AOR = 0.49; 95 % CI: 0.30-0.82), primary education (AOR = 0.39; 95 % CI: 0.18-0.81), wish to become pregnant (AOR = 2.57; 95 % CI: 1.64 to 4.02), no history of contraceptive use (AOR = 2.01; 95 % CI: 1.19 to 3.38), no counselling on benefits (AOR = 1.68; 95 % CI: 1.08-2.62), and side effects (AOR = 1.95; 95 % CI: 1.21-3.16) were the factors associated with discontinuation. Conclusion: The overall discontinuation of implants was low compared to the 2016 Ethiopian Demographic Health Survey. Education, desire for pregnancy, no history of contraceptives, lack of counselling on benefits, and side effects were factors for discontinuation.